2017
DOI: 10.1016/j.imbio.2016.10.006
|View full text |Cite
|
Sign up to set email alerts
|

The non-mammalian MIF superfamily

Abstract: Macrophage migration inhibitory factor (MIF) was first described as a cytokine 50 years ago, and emerged in mammals as a pleiotropic protein with pro-inflammatory, chemotactic, and growth-promoting activities. In addition, MIF has gained substantial attention as a pivotal upstream mediator of innate and adaptive immune responses and with pathologic roles in several diseases. Of less importance in mammals is an intrinsic but non-physiologic enzymatic activity that points to MIF's evolution from an ancient defen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 111 publications
(98 reference statements)
0
45
0
Order By: Relevance
“…Furthermore, MIF proteins are characterized by a unique enzymatic tautomerase activity at University of Groningen on January 13, 2020 http://www.jbc.org/ Downloaded from that is unprecedented in the chemokine-/cytokine group of proteins, and that is a notable component of the remarkable evolutionary conservation of the MIF sequence (8,25,61). MIF has been implicated as a player in various host-parasite interactions and MIF orthologs have been predicted to exist even in the plant kingdom (32,33,38).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, MIF proteins are characterized by a unique enzymatic tautomerase activity at University of Groningen on January 13, 2020 http://www.jbc.org/ Downloaded from that is unprecedented in the chemokine-/cytokine group of proteins, and that is a notable component of the remarkable evolutionary conservation of the MIF sequence (8,25,61). MIF has been implicated as a player in various host-parasite interactions and MIF orthologs have been predicted to exist even in the plant kingdom (32,33,38).…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, this appears unlikely, as plants do not express a major histocompatibility (MHC) system. However, CD74 has been found to be an amenable target of parasite MIF orthologs such as leishmania, plasmodium, or hookworm (32,35,37,71,72), suggesting that it is a receptor molecule prone to be engaged during host-parasite interactions. In fact, it has been suggested that the MIF binding functionality of CD74, which is best known as the MHC class II chaperone invariant chain Ii, already represents a "secondary" function of this membrane protein (16,73).…”
Section: Although Interactions Betweenmentioning
confidence: 99%
See 2 more Smart Citations
“…The discovery of Leishmania-encoded MIF orthologs is not entirely surprising, as MIF orthologs are found in organisms at all positions of the evolutionary tree, including protozoa, nematodes, plants, and invertebrate and vertebrate mammals alike. Furthermore, MIF orthologs have been reported in dozens of species of protozoan and helminthic parasites, and their properties have been thoroughly explored [100][101][102].…”
Section: Overview Of Mif Orthologs In Leishmania and Other Parasitesmentioning
confidence: 99%